Novaia studiia . Novaia studiia . New Studio . Новая студия - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the work of the journalists of "Novaia Studia" ("New Studio") during the season of 1992-1993; concert; excerpts from the programs "IA" ("I"); "Press-Club"; "Vybor 2000" ("Choice 2000"). Contributors: Pushkina, Tat'iana (Anchor); Proshutinskaia, Kira Aleksandrovna (Anchor) Обсуждение работы журналистов"Новой студии" за сезон 1992-1993; концерт; отрывки из передач "Я", "Пресс-клуб", "Выбор 2000.". Создатели: Пушкина, Татьяна (Ведущий/Ведущая); Прошутинская, Кира Александровна (Ведущий/Ведущая)